Removal of a Calcium Silicate-Based Sealer from Oval Root Canals Using Different Irrigation Activation Techniques: A Stereomicroscopic and SEM–EDS Study - Merfea, Mihai; Cimpean, Sanda Ileana; Pop-Ciutrila, Ioana Sofia; Assaf, Elie; Delean, Ada Gabriela; Badea, Iulia Clara; Cuc, Stanca; Surdu, Vasile Adrian (MDPI AG, 2026)
Calcium silicate-based sealers are widely used in contemporary endodontics, but their strong interaction with dentinal substrates may complicate their removal during nonsurgical retreatment and potentially hinder canal disinfection. This ex vivo study evaluated the effectiveness of different irrigation activation techniques in removing a calcium silicate-based sealer from oval-shaped root canals. Sixty extracted single-rooted teeth were instrumented and obturated using the single-cone technique with NeoSealer Flo, followed by retreatment using a reciprocating system. Specimens were randomly assigned to four final irrigation protocols: conventional needle irrigation (CNI) with NaOCl/EDTA, ultrasonic activation (US), diode laser activation (LI), and Er:YAG laser activation using the SWEEPS mode (SW) (n = 15). Residual filling material was quantified before and after final irrigation using stereomicroscopic imaging and ImageJ (version 1.54) analysis. Dentinal surface morphology and residual sealer were further evaluated using SEM–EDS. Statistical analysis included one-way ANOVA and chi-square tests (p < 0.05). All protocols significantly reduced residual filling material compared with mechanical retreatment alone (US 15.08%, CNI 7.89%, LI 8.01%, SW 7.20%) (p < 0.01). US resulted in significantly greater sealer removal compared with CNI, LI, and SW, with mean differences ranging from 7.08% to 7.88% (p < 0.05). These findings indicate that irrigation activation enhances the removal of NeoSealer Flo calcium silicate-based sealer, with ultrasonic activation demonstrating greater effectiveness among the evaluated techniques, under the conditions of this experimental setup.
Keywords: bioceramic sealer; calcium silicate sealer; endodontic retreatment; irrigation activation; ultrasonic irrigation; SWEEPS laser; SEM–EDS